2017
DOI: 10.1002/jcc.25054
|View full text |Cite
|
Sign up to set email alerts
|

Rhorix: An interface between quantum chemical topology and the 3D graphics program blender

Abstract: Chemical research is assisted by the creation of visual representations that map concepts (such as atoms and bonds) to 3D objects. These concepts are rooted in chemical theory that predates routine solution of the Schrödinger equation for systems of interesting size. The method of Quantum Chemical Topology (QCT) provides an alternative, parameter‐free means to understand chemical phenomena directly from quantum mechanical principles. Representation of the topological elements of QCT has lagged behind the best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…The suitability of this assumption will be tested. All QCT images were generated with Rhorix, , a plugin for Blender, using data computed with AIMAll. Molecular graphics were created using the program Visual Molecular Dynamics (VMD) , and its internal ray tracer.…”
Section: Background and Methodsmentioning
confidence: 99%
“…The suitability of this assumption will be tested. All QCT images were generated with Rhorix, , a plugin for Blender, using data computed with AIMAll. Molecular graphics were created using the program Visual Molecular Dynamics (VMD) , and its internal ray tracer.…”
Section: Background and Methodsmentioning
confidence: 99%
“…46,66 The electrostatic interaction energy calculated at rank L can be regarded as "reference" or "exact" multipolar energy if the standard of eq 4 is met. All QCT images were obtained by Rhorix, 67,68 utilizing the data calculated with AIMAll. Molecular graphics were generated with the program visual molecular dynamics (VMD).…”
Section: ■ Background and Methodsmentioning
confidence: 99%
“…This convergence criterion is more severe compared to that used in the existing force fields. ,, However, for some atom–atom interactions, when the electrostatic energy hovers closely around the exact electrostatic energy (6D value), the phenomenon of “pseudoconvergence” may emerge. , The electrostatic interaction energy calculated at rank L can be regarded as “reference” or “exact” multipolar energy if the standard of eq is met. All QCT images were obtained by Rhorix, , utilizing the data calculated with AIMAll. Molecular graphics were generated with the program visual molecular dynamics (VMD). , …”
Section: Background and Methodsmentioning
confidence: 99%
“…This is also by research which shows that modeling the crystal structure of cellulose with the help of spreadsheets will produce attractive and interactive visualization of images [31]. Other studies have also revealed that visualizing crystal structures using a blender software can produce a movable three-dimensional visualization of crystal structures, making it more interactive and communicative which can increase students' interest in learning it [32]. The opinions expressed by the six assessors are in principle correct, but the purpose of this crystal structure modeling is to improve the psychomotor abilities and creativity of students.…”
Section: Figure 2 Molymod-assisted Crystal Structure Modelling (A) Carbon Tetrachloride (B) Diamond and (C) Fullerenesmentioning
confidence: 97%